Animal sound activity detection using support vector machines - Salami, Momoh Jimoh Emiyoka (s.n, 2012)
In this research, effects of different level of frequencies as precursor to earthquakes have been investigated. Thus, an artificial station for studying and predicting earthquake and Tsunami using unusual animal behaviors has been developed for monitoring unusual animal behavior and classification done using support vectors machines